Relasi Gender dalam Pernikahan Keturunan Sayyid di Desa Cikoang Kabupaten Takalar; Studi Kasus Perbandingan Hukum Islam Dan Hukum Adat - Mustafa, Adriana; Bahram, Arwini (Mazahibuna: Jurnal Perbandingan Mazhab, 2020)
Islamic law holds that the concept of kafaah comes from various aspects, namely religion, descent, property, and face. Among these four things, Sharia prioritizes religion as the main yardstick in determining the concept of kaffah. On the other hand, customary law views that the marriage of sayye descendants in a society still maintains their familiarity, system and belief in the descendants of the Prophet Muhammad. rules that have become absolute and nothing can be seen. However, the marriage system becomes a problem because it can exclude women, and their rights as women. The purpose of this study was to examine and trace the ins and outs of the Sayye marriage system so that gender relations were born among the Sayye community. The research method used is field research and is qualitative and comparative. Sources of data used in this study come from primary and secondary data. The result of this research is that the form of Sayyid's marriage gender relation has the right to determine in his life